(Cr2/3Ti1/3)3AlC2 and (Cr5/8Ti3/8)4AlC3: New MAX‐phase Compounds in Ti–Cr–Al–C System. Issue 1 (12th December 2013) - Liu, Zhimou; Zheng, Liya; Sun, Luchao; Qian, Yuhai; Wang, Jingyang; Li, Meishuan
Abstract : Two new MAX compounds, (Cr2/3 Ti1/3 )3 AlC2 and (Cr5/8 Ti3/8 )4 AlC3, were successfully synthesized by hot‐pressing elemental powders at 1500°C for 1 h under 30 MPa in a flowing argon atmosphere. Their crystal structures were indentified and characterized by X‐ray diffraction and transmission electron microscopy analysis. (Cr2/3 Ti1/3 )3 AlC2 and (Cr5/8 Ti3/8 )4 AlC3 have the same crystal structures with the well‐characterized Ti3 AlC2 and Ti4 AlN3, respectively.